2015
DOI: 10.1002/cctc.201500710
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Fluorescence Tomography of Aged Fluid‐Catalytic‐Cracking Catalyst Particles Reveals Insight into Metal Deposition Processes

Abstract: Microprobe X-ray fluorescence tomography was used to investigate metal poison deposition in individual, intact and industrially deactivated fluid catalytic cracking (FCC) particles at two differing catalytic life-stages. 3 D multi-element imaging, at submicron resolution was achieved by using a large-array Maia fluorescence detector. Our results show that Fe, Ni and Ca have significant concentration at the exterior of the FCC catalyst particle and are highly co-localized. As concentrations increase as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 54 publications
(106 reference statements)
2
65
0
Order By: Relevance
“…1, the morphological information obtained by nano-TXM is displayed. The particle appears to be a typical FCC catalyst particle when compared with previous studies181920212941: it has a diameter of about 40 μm, shows a denser surface layer of 1–2 μm thickness and a complex macro-pore structure throughout the rest of the particle; the total porosity was determined to 18.8%. In this study, we additionally performed a pore throat analysis45, which revealed a pore throat size distribution peak at about 320 nm.…”
Section: Resultsmentioning
confidence: 58%
“…1, the morphological information obtained by nano-TXM is displayed. The particle appears to be a typical FCC catalyst particle when compared with previous studies181920212941: it has a diameter of about 40 μm, shows a denser surface layer of 1–2 μm thickness and a complex macro-pore structure throughout the rest of the particle; the total porosity was determined to 18.8%. In this study, we additionally performed a pore throat analysis45, which revealed a pore throat size distribution peak at about 320 nm.…”
Section: Resultsmentioning
confidence: 58%
“…[18,19] During the FCC process, the catalyst deactivates irreversibly due to dealumination and the accumulation of metals, mainly Fe, Ni, and V. While Ni and V decrease the yield by promoting for example, coke formation, Fe is supposed to deactivate the particles by creating a shell of reduced porosity on the particles outer surface, either via vitrification of the particle matrix in the presence of Fe and/or co-deposition of silica. [20][21][22][23][24][25][26][27][28][29] Therefore, during operation, to create a stable process efficiency, a fraction of catalyst is being replaced on a daily basis, resulting in a mixture called equilibrium catalyst (ECAT). To investigate their deactivation, FCC ECAT particles are often sorted based on their skeletal density, which is associated with metal loading and age.…”
Section: Recent Advances In Microfluidics Open New Ways To Workmentioning
confidence: 99%
“…4,[7][8][9] Until recently, limited academic research has been reported on such industrial catalysts, but a spate in the development of advanced characterization techniques able to probe the multi-dimensional parameters of these materials with high spatiotemporal resolution (and also non-invasively) has provided signicant insights into the structure-performance relationships of these closely guarded materials. [10][11][12][13][14][15][16][17][18][19][20] Particularly in the eld of Fluid Catalytic Cracking (FCC) particles and zeolite-based binder-bound extrudates and pellets for e.g. methanol-tohydrocarbon (MTH) catalysis, combinations of chemical imaging and structural imaging techniques, together with standard physicochemical characterization of the materials, have enhanced our knowledge into how these complex materials function.…”
Section: Introductionmentioning
confidence: 99%